The JAK2 V617F mutational status and allele burden may be related with the risk of venous thromboembolic events in patients with Philadelphia-negative myeloproliferative neoplasms. Issue 2 (February 2015) - Borowczyk, Martyna; Wojtaszewska, Marzena; Lewandowski, Krzysztof; Gil, Lidia; Lewandowska, Maria; Lehmann-Kopydłowska, Agata; Kroll-Balcerzak, Renata; Balcerzak, Andrzej; Iwoła, Małgorzata; Michalak, Michał; Komarnicki, Mieczysław
Abstract: Introduction: Patients with Philadelphia-negative myeloproliferative neoplasms (Ph - MPNs) are at increased risk of thromboembolic and hemorrhagic complications. The aim of the study was to determine the relationship between JAK2 V617F mutational status, JAK2 V617F allele burden and the risk of vascular complications occurrence. Materials and methods: Analysis was performed in a cohort of 186 patients diagnosed with polycythemia vera (53), essential thrombocythemia (114), primary myelofibrosis (11), and unclassified MPN (8). The risk of vascular complications development was analyzed in 126 JAK2 V617F-positive patients with respect to allele burden assessed with allele-specific 'real-time' quantitative polymerase chain reaction (AS RQ-PCR). Results: Overall prevalence of any vascular complications was 44.6%. Arterial thrombosis occurred in 20.4%, venous thromboembolism (VTE) in 11.3%, bleeding episodes in 24.7% of patients. Individuals harboring JAK2 V617F mutation, regardless of MPN type, were at higher risk of VTE (OR = 5.15, 95%CI: 1.16-22.90, P = 0.024), mainly deep vein thrombosis (DVT). JAK2 allele burden higher than 20% identified patients with 7.4-fold increased risk of VTE (95%CI: 1.6-33.7, P = 0.004), but not of arterial thrombosis, neither of bleeding complications, and remained the only significant VTE risk factor in multivariate logistic regression. High allele burdens (over 50%) were strikingly associated with proximal DVT cases, but not with distal DVT. Conclusions: The group of MPN patients with JAK2 V617F allele burden higher than 20% may benefit the most from vigilant monitoring and appropriate prophylaxis against vascular events. Inclusion of JAK2 V617F mutant allele burden in new risk stratifications seems to be justified and requires controlled prospective trials. Highlights: JAK2 V617F allele burden > 20% identifies patients with an increased risk of VTE. Those patients are mainly at increased risk of DVT, but not of bleeding. They may benefit the most from appropriate prophylaxis against vascular events. High allele burdens are associated with proximal DVT, but not with distal DVT cases. The allele burden should be included in new risk stratification scoring systems.